Ethnomedicinal practices in the arid zone of India: A study in urban and semi-urban areas of Bhuj, Gujarat - Gajjar, Dipmala; Poptani, Rakesh; Paradva, Bhagirath; Mahato, Arun Kumar Roy; Bhatt, Jayesh B. (Current Botany, 2023)
Plants are a vital and life-sustaining natural resource as they provide many ecosystem services and supply food, fibre, fuel, medicine, etc. They are distributed heterogeneously in different ecosystems. With the increasing urbanization in all parts of the world, the vegetation overlapped with urban localities like parks, gardens, roadsides, wasteland and other human habitations. Among this vegetation, many of them are used in ethnomedicine or in ayurvedic medicine by people for a long period of time. These valuable plant resources are now under threat due to various anthropogenic activities in the urban landscape. Bhuj is a small historic city in the arid zone of India with a rich diversity of medicinal plants. With the increasing human population and associated developmental activities within the city, many of these plants are under threat of extinction. Therefore, an attempt was made to document these medicinal plants distributed in different parts of the city and their uses for ethnomedicinal purposes. The plants were intensively surveyed and documented using a questionnaire survey, discussion and cross-checked with available literature. A total of 123 species of ethnomedicinal plants were documented and analysed for their uses in curing different health problems and conservation purposes in the urban landscape.